The College Academic Service Decision Support System Uses Service Quality and Importance-Performance Analysis Methods - Beny Irawan; Raden Aldri Kurnia; Erwin Daniel Sitanggang; Misdem Sembiring (INFOKUM, 2021)
The impact of the Covid-19 pandemic that has hit the world affects human needs in utilizing technology to be able to solve the problems they face. Likewise, universities that want to improve the quality of academic services during a pandemic sometimes have problems with accuracy and speed in data processing when measuring the level of student satisfaction whose information will be used as support in making decisions to improve services. It is better to develop a computerized system that can replace all activities in the process of implementing the measurement of academic service quality from distributing questionnaires to getting the results of Service Quality (Servqual) and Importance-Performance Analysis (IPA) analysis using the Unified Modeling Language (UML) approach. The design of the decision support system used in this design, namely: Use Case Diagrams, Class Diagrams, Activity Diagrams, Sequence Diagrams and Deployment Diagrams. By using a computerized decision support system, the process of measuring the level of student satisfaction with academic services can be carried out quickly, precisely and accurately compared to using word processing and spreadsheet software and provides easy-to-understand information and suggestions for improvement. academic services based on the attributes of the questionnaire accurately using the Service Quality (Servqual) method on Gap 5 and Importance-Performance Analysis (IPA).